Risk Profile Assessment ofRisk profile assessment of core capital adequacy: capital adequacy tier-book strategy Core Capital Adequacy: Capital Adequacy Tier-Book Strategy - Lis Sintha Oppusunggu; Yusuf Rombe M.Allo (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The purpose of this study is to analyze the effect of risk profile variables both on the fulfillment of core capital adequacy and to find out which risk variables have a dominant influence on core capital adequacy in bank books 1 and 2. This research is included in quantitative analysis. This study uses purposive sampling, and data collection is carried out using the documentation method by looking at the annual financial reports on the OJK (Financial Services Authority) website, BI (Bank Indonesia) website, and the Bank's website object of research. The results of this study using the level of capital ratios by banks, namely the ratio of CAR, ROA, OEOI, NIM, LDR, and RAR, show good results. Because the standard deviation reflects very high variations, the distribution of data shows expected results and does not cause bias. Assessment of the Bank's Soundness Level using a risk approach (Risk-based Bank Rating) is executed based on a thorough analysis of the Bank's performance, risk profile, problems, and development prospects of the Bank since the purpose of maintaining the soundness of banks through consideration of the aspect of capital adequacy is the most significant part in order to gain public trust.